2022
DOI: 10.17323/jle.2022.15962
|View full text |Cite
|
Sign up to set email alerts
|

Towards Understanding Teacher Mentoring, Learner WCF Beliefs, and Learner Revision Practices Through Peer Review Feedback: A Sociocultural Perspective

Abstract: Background. The existing literature has focused on learner perceptions or beliefs about peer review tasks over the recent decade. However, little has been known about the relationships among learner beliefs about written corrective feedback (WCF), related teacher mentoring process, and learner revision practices. Purpose. We thus aimed at addressing the gap by exploring how teacher mentoring and learner WCF beliefs may inform learner revision practices in the peer-reviewed process. Methods. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…This exploration should be guided by an active approach to learning, where learners seek out or create opportunities to use these models in contextually meaningful ways, such as writing practice, reading comprehension, and conversational simulations [1]. Moreover, the social influence factor suggests the benefit of forming study groups or online communities where learners can share tips, resources, and experiences related to using large language models for vocabulary learning [35]. Such collective efforts can not only improve individual learning outcomes but also contribute to a more collaborative and supportive learning environment [36].…”
Section: Discussionmentioning
confidence: 99%
“…This exploration should be guided by an active approach to learning, where learners seek out or create opportunities to use these models in contextually meaningful ways, such as writing practice, reading comprehension, and conversational simulations [1]. Moreover, the social influence factor suggests the benefit of forming study groups or online communities where learners can share tips, resources, and experiences related to using large language models for vocabulary learning [35]. Such collective efforts can not only improve individual learning outcomes but also contribute to a more collaborative and supportive learning environment [36].…”
Section: Discussionmentioning
confidence: 99%
“…Academic English course is a compulsory course for college and postgraduate students. Academic English courses in English-speaking countries aim to assist students in comprehending academic language and preparing for professional job [ 8 , 9 ]. Due to different understandings of academic English courses, some universities in non-English speaking countries focus primarily on teaching academic English grammar, while others emphasize academic English writing and reading [ 10 , 11 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, researchers have found that digital multitasking could facilitate the development of a "checking habit", which could impact students' concentration [17], generating distractions and course work conflicts [18], and even influencing overall college GPA [6,[19][20][21]. Meanwhile, many researchers tried to examine the nature and the major mediator behind such behavior [22]. For instance, researchers believed that more exposure to digital devices would cause physical stimulation to students and then increase the tendency of digital multitasking in class, called "technology addiction" [11].…”
Section: Introductionmentioning
confidence: 99%